If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4 = 5x + 3 Reorder the terms: -4 + 6x = 5x + 3 Reorder the terms: -4 + 6x = 3 + 5x Solving -4 + 6x = 3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -4 + 6x + -5x = 3 + 5x + -5x Combine like terms: 6x + -5x = 1x -4 + 1x = 3 + 5x + -5x Combine like terms: 5x + -5x = 0 -4 + 1x = 3 + 0 -4 + 1x = 3 Add '4' to each side of the equation. -4 + 4 + 1x = 3 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 3 + 4 1x = 3 + 4 Combine like terms: 3 + 4 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| -3*(-5)*(-3)*(-5)= | | 9x-6=7x+10 | | 8x-9x-3=24 | | 5(2x-5)-(4x-7)=-10 | | 4x+21=8x-3 | | 3(x-3)=x+19 | | -16x^2+32x+128=0 | | y=7x^3-3x^2-56x+24 | | 6x-48+18=3x-12 | | 4-3m^2-m^3=0 | | 70+14x=16x | | 6x+1=5+5x | | 3x+5(-3x-4)=-23-9x | | y=3x^3-4x^2-22x+21 | | 4n+3=6n-17 | | 0.2x-0.9x-8=41 | | 6x+15=6x+7 | | 12=ln(3y-7) | | (3x+k)(9x^2+21x+k^2)=27x^3+k^3 | | 5(3x-8)=10x+6 | | 5(2x-3)=6 | | x+7.7=12.2 | | 2x^2+8x=12 | | 5x+7-2=2x+10+x | | 35x^4-30x^2+3=0 | | 4x-15=145 | | 36=2 | | xsquared=6x+8 | | 9(6x+7)= | | -4x-14+5x=4 | | 4v-4=-12 | | 4x+6(-2x-3)=-23-3x |